Reorganization energy in the discharge of palladium(II) hydroxyethyliminodiacetate complexes - Kublanovsky, V. S.; Nikitenko, V.N.; Rudenko, K. P. (Reports of the National Academy of Sciences of Ukraine, 2014)
The total reorganization energy of a system and its components (the solvent reorganization energy and the rearrangement energy of the first coordination sphere of a reacting complex ion in the reduction of palladium (II) hydroxyethyliminodiacetate complexes) have been calculated. The calculated values of solvent reorganization energy and the reorganization energy of the first coordination sphere of complex ion [Pd(heida)2]2− are in agreement with the Marcus and Dogonadze–Kuznetsov theory. An experimental method for the analysis of current – potential curves in the Marcus coordinates is proposed. It allows one to estimate the total energy of reorganization in the reduction of coordination ions. The dependence of the total reorganization energy of the system on the temperature of the hydroxyethyliminodiacetate electrolyte has been established. The experimental data obtained are in good agreement with calculated ones.